Key factors influencing women micro-entrepreneurs to use Ar-Rahnu: evidence from Siti Khadijah’s Market, Kelantan - Nik Azman, Nik Hadiyan; Kassim, Salina; Masron, Tajul Ariffin (INSI Publications, 2015)
Ar-Rahnu is becoming an increasingly micro-credit instrument in Malaysia. It is accepted as a viable and competitive mode to obtain cash instantly. Despite this, studies on Ar-Rahnu, particularly on the acceptance factors among women micro-entrepreneurs has been very limited. This study aims to investigate the level of acceptance for ArRahnu among women micro-entrepreneurs, in Siti Khadijah’s market, Kelantan. This study conducted in-depth interviews with the women micro-entrepreneurs from different area of business who used Ar-Rahnu as a source of capital. Overall, there are four sub themes influencing the acceptance of Ar-Rahnu, namely; locality, difficulties in getting loan, service charges and collateral. This study finds that, service charge is the main factor influencing women micro-entrepreneurs to choose Ar-Rahnu as their source of micro-credit.